Jabatan Kerja Raya (JKR), Daerah Muar / Mohamad Hafizuddin Hakim Zainal - Zainal, Mohamad Hafizuddin Hakim (UiTM Johor Pasir Gudang, 2018)
As a student from Universiti Teknologi Mara (UiTM) Cawangan Johor Kampus Pasir Gudang, Faculty of Civil Engineering, I need to go to the industrial training. This report describes my industrial training experience. The aim of the industrial training is to expose students to the reality of employment and to enhance their knowledge on how to manage an organization or industry. It also gives them an opportunity to apply the theories learned while being in the real world of employment.